Integrated planning for the resilience of urban riverine ecosystems: the Istanbul-Omerli Watershed case - Tezer, Azime; Sen, Omer Lutfi; Aksehirli, like; Cetin, Nuket Ipek; Onur, Aliye Ceren Tan (Elsevier BV, 2012)
Abstract Since urban areas display nonlinear and dynamic interactions within their growth patterns, a crucial question is how complex systems can be integrated into urban planning practices in relation to urban ecosystems. Natural threats and extreme weather conditions resulting from climate change will threaten social, environmental and economic assets in urban riverine ecosystems due to their cumulative vulnerabilities, especially in less developed regions. This paper will discuss an “ecosystem services based watershed management framework” to increase the resilience capacity of urban riverine systems using the case of the Omerli Watershed (Turkey), which is located in a metropolitan area characterized by rapid population growth and ecosystem change. Three research domains, i.e. ecosystem services (ESs), spatial planning and climate change (CC) mitigation, will be integrated in order to propose an analytical methodology for spatial planning of urban riverine systems. The adaptive mitigation approach is used to accommodate both mitigation and adaptation policies in its structure. The methodology used here is a part of an ongoing research effort. However, this assessment is aimed at clarifying the integration of the three research domains for use in policy development.